Perilaku Konsumen Terhadap Sertifikasi Halal Pada Makanan Di Kota Makassar - Dzulfadlin, Prawira Aditya; Alam, Andi Rifqah Purnama (Patria Artha Management Journal, 2020)
This study aims to determine the effect of consumer behavior regarding halal certification on food on purchase intention in Makassar City. Sources of data in this study are primary data and secondary data as well as data collection methods by interview and questionnaire. The sample in this study were 155 people with the simple random sampling method. The data analysis method used is simple linear regression analysis. The results showed that consumer behavior regarding halal certification had a significant effect on people's buying interest as indicated by the equation Y = 0.001 + 0.797X with a significance value of 0.000 <0.005, so the hypothesis in this study was accepted.